Academic library spaces in the new learning ecosystem - González-Fernández-Villavicencio, Nieves (Anuario ThinkEPI, 2017)
Academic library spaces are transforming to adapt to new forms of learning, while at the same time the library print-collections, with reduced or zero use, are being moved to library marginal zones or to sites that are external to library buildings. The causes of transformation to library spaces are described, as well as the consequences that this transformation implies in new forms of collection storage, and the supply of new and diverse learning spaces, without limiting access to information.
Keywords: Physical library spaces; Off-site storage; External storage; Learning; Print-collections; Quiet spaces.